2011
DOI: 10.1039/c1ob05783a
|View full text |Cite
|
Sign up to set email alerts
|

Generation of diverse 2-pyrones via palladium-catalyzed site-selective Suzuki-Miyaura couplings of 3-bromo-4-tosyloxy-2-pyrone

Abstract: Based on different reactivity of the (pseudo)halide substituents in the 2-pyrone (3-Br and 4-OTs), palladium-catalyzed sequential site-selective Suzuki-Miyaura cross-coupling reactions of 3-bromo-6-methyl-4-tosyloxy-2-pyrone are described, which afford the diverse 2-pyrones in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 68 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…In a complementary exploration of C-3 functionalisation 5a was brominated (Br 2 , CHCl 3 , 72 h, reflux) to afford 7 in 73% yield. Guided by reaction conditions employed by Wu et al, for the 3-arylation of 3-bromopyran-2-ones 23 the Suzuki crosscoupling of 7 with arylboronic acids gave 6a (40%), 6b (58%) and 6c (36%) (unoptimized yields); it is noteworthy that the highest yield for the Suzuki cross-coupling reaction was recorded with the electron rich 4-methoxyphenylboronic acid and complements the C-H bond functionalisation where the best yield was noted for electron deficient coupling partners. Bromination of 5b was marginally more effective, though did require the addition of pyridine (0.25 eq.)…”
Section: Resultsmentioning
confidence: 99%
“…In a complementary exploration of C-3 functionalisation 5a was brominated (Br 2 , CHCl 3 , 72 h, reflux) to afford 7 in 73% yield. Guided by reaction conditions employed by Wu et al, for the 3-arylation of 3-bromopyran-2-ones 23 the Suzuki crosscoupling of 7 with arylboronic acids gave 6a (40%), 6b (58%) and 6c (36%) (unoptimized yields); it is noteworthy that the highest yield for the Suzuki cross-coupling reaction was recorded with the electron rich 4-methoxyphenylboronic acid and complements the C-H bond functionalisation where the best yield was noted for electron deficient coupling partners. Bromination of 5b was marginally more effective, though did require the addition of pyridine (0.25 eq.)…”
Section: Resultsmentioning
confidence: 99%
“…Lei et al. have reported that 3‐bromo‐6‐methyl‐4‐tosyloxy‐2‐pyrone undergoes Pd 2 (dba) 3 /Johnphos‐catalyzed chemoselective C‐3 arylation with arylboronic acids and that the resulting cross‐coupling products provide 3,4‐diaryl‐6‐methyl‐2‐pyrones bearing different aryl groups in good overall yields by Pd(OAc) 2 /PCy 3 ‐catalyzed Suzuki–Miyaura cross‐coupling reactions with different arylboronic acids 213…”
Section: Discussionmentioning
confidence: 99%
“…This approach has also been used to prepare substituted 2-pyranones (Scheme S5). 16 The starting compound S5-1 was reacted with arylboronic acids under distinct reaction conditions to accomplish the synthesis of the target molecules. In the first step, the bromine atom was substituted using Pd 2 (dba) 3 and (2-biphenyl)di-tertbutylphosphine (JohnPhos).…”
Section: Scheme S4 Stereoselective Synthesis Of Terminal Vinyl Monoflmentioning
confidence: 99%